A Green Intervention in Media Production Culture Studies: Environmental Values, Political Economy and Mobile Production. (1st April 2021) - Vaughan, Hunter
Abstract : This article develops an interdisciplinary theoretical method for assessing the environmental values articulated and practised by dispersive or 'mobile' film production practices, aiming toward applicable strategies to make media practices more environmentally conscientious and sustainable. Providing a social and environmental study of the local relational values, political economy and ecosystem ramifications of runaway productions and film incentive programmes, this study draws on contemporary international green production practices as entryways into environmentally positive film industry change. Offering an overview of the potential use of a relational values approach to media production cultures, the essay uses two opposing models (the Michigan film incentive and the underwater cinematography culture of South Florida) in order to assess the political dynamics, social consequences and environmental threats of Hollywood's mobile practices - as well as their potential as sites, beyond Hollywood, to converge environmental values with local media culture.